Frequency Modulated Continuous Wave Radar System and Identity and Information Detection Method Thereof (2021)
A frequency modulated continuous wave radar system includes at least one identity tag, respectively disposed next to at least one test subject; and a frequency modulated continuous wave radar identity recognition device, including an identity recognition control module, for controlling a test identity tag of the at least one identity tag to be turned on to generate a specific tag reflection signal corresponding to an identity frequency in response to a chirp signal; and a frequency modulated continuous wave radar, for transmitting the chirp signal and receiving at least one reflection signal of the at least one test subject and the specific tag reflection signal in response to the chirp signal, to calculate and determine that the specific tag reflection signal and a specific reflection signal of the at least one reflection signal are corresponding to an adjacent position information. The specific reflection signal is corresponding to test subject information.